Invisible light inside the natural blind spot alters brightness at a remote location - Marina Saito (Nature Portfolio, 2018)
Abstract The natural blind spot in the visual field has been known as a large oval region that cannot receive any optical input because it corresponds to the retinal optic disk containing no rod/cone-photoreceptors. Recently, stimulation inside the blind spot was found to enhance, but not trigger, the pupillary light reflex. However, it is unknown whether blind-spot stimulation also affects visual perception. We addressed this question using psychophysical brightness-matching experiments. We found that a test stimulus outside the blind spot was judged as darker when it was accompanied by a consciously unexperienced blue oval inside the blind spot; moreover, the pupillary light reflex was enhanced. These findings suggested that a photo-sensitive mechanism inside the optic disk, presumably involving the photopigment melanopsin, contributes to our image-forming vision and provides a ‘reference’ for calibrating the perceived brightness of visual objects.